Liver Abscess Severity at Slaughter Does Not Affect Meat Tenderness and Sensory Attributes in Commercially Finished Beef Cattle Fed Without Tylosin Phosphate - E. J. McCoy; T. G. O'Quinn; E. F. Schwandt; C. D. Reinhardt; D. U. Thomson (Kansas Agricultural Experiment Station Research Reports, 2017)
Liver abscesses are a significant problem in the United States’ cattle feeding industry, costing the industry an estimated $15.9 million annually in liver condemnation, trim losses, and reduced carcass weights and quality grades. Recent reported incidence rates of liver abscesses at slaughter range from 10 to 20%. Liver abscess incidence may be influenced by a number of factors including: breed, gender, diet, days on feed, cattle type, season, and geographical location. Liver abscesses typically occur secondary to rumen insults caused by acidosis or rumenitis. It has been proposed that pathogens associated with liver abscess formation enter the blood stream through damaged rumen epithelium and are transported to the liver through the portal vein where they cause infection, manifested as liver abscesses. Severe liver abscesses have been linked to reduction in hot carcass weight, dressing percentage, yield grade, longissimus muscle area, and marbling scores of carcasses when compared to those with normal livers. However, the effect of liver abscesses on meat tenderness and sensory attributes has not been previously investigated.
Keywords: cattle; liver abscesses; meat tenderness